Any day now [large type] - Carr, Robyn (Carr, Robyn. Sullivan's Crossing, 2017)
For Sierra Jones, Sullivan's Crossing is meant to be a brief stopover. She's put her troubled past behind her but the path forward isn't yet clear. A visit with her big brother Cal and his new bride, Maggie, seems to be the best option to help her get back on her feet. Not wanting to burden or depend on anyone, Sierra is surprised to find the Crossing offers so much more than a place to rest her head. Cal and Maggie welcome her into their busy lives and she quickly finds herself bonding with Sully, the quirky campground owner who is the father figure she's always wanted. But when her past catches up with her, it's a special man and an adorable puppy who give her the strength to face the truth and fight for a brighter future. In Sullivan's Crossing Sierra learns to cherish the family you are given and the family you choose